Analysis Of Learning Using The Think-Pair-Share Model On Students' Social Interaction - Ummi Salmah; Husarida Husarida (At- Ta'lim : Jurnal Pendidikan, 2026)
This study aims to analyze student social interaction in Al-Qur'an Hadith learning through the application of the Think-Pair-Share (TPS) cooperative learning model. The study used a qualitative approach with a descriptive method conducted in class VIII MTs Negeri 1 Tanjung Jabung Timur. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive model that included data reduction, data presentation, and conclusion drawing. The results showed that the application of the TPS model was able to create a more active, interactive, and enjoyable learning atmosphere. Students' social interactions developed through paired discussions, group work, class presentations, and mutual respect for opinions. Each stage in the TPS model had a different contribution, namely the think stage trained independent thinking, the pair stage encouraged cooperation and exchange of ideas, and the share stage increased the courage to express opinions and communication skills. In addition, the role of the teacher as a facilitator proved to be important in managing classroom dynamics and encouraging student participation. However, this study also found that the level of student participation was not yet evenly distributed due to differences in motivation and self-confidence. Therefore, a more inclusive classroom management strategy is needed so that all students can be optimally involved in cooperative learning.